Pengaruh Budaya Organisasi dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor Wilayah Kementerian Agama DKI Jakarta - Difa Abril Umam; Sofyan Marwansyah (PT. Karya Inovatif Nusantara, 2026)
The Jakarta Regional Office of the Ministry of Religious Affairs is the representative of the Ministry of Religious Affairs of the Republic of Indonesia at the provincial level, tasked with implementing policies in the religious field. Employee performance is a fundamental factor in supporting this task, which is influenced by several important factors, namely organizational culture and work discipline. Organizational culture shapes patterns of thinking and acting, while work discipline encourages responsibility in completing tasks. This study aims to determine the influence of organizational culture and work discipline on employee performance at the Jakarta Regional Office of the Ministry of Religious Affairs. This study uses a quantitative approach. The sample consisted of 46 respondents. Data collection was carried out through questionnaires. The results of the t-test indicate that partially organizational culture has a significant effect on employee performance (t count 5.676 > t table 2.017), while work discipline has no significant effect (t count 1.554 < t table 2.017). The results of the F-test indicate that simultaneously organizational culture and work discipline have a significant effect on employee performance (F count 31.488 > F table 3.21), a significant value (0.001 < 0.05).